Pemetaan Riset Manajemen Konstruksi di Kota Manokwari Berbasis Roadmap Penelitian Jurusan Teknik Sipil tahun 2025-2030 - Indra Birawaputra (JISTECH: Journal of Information Science and Technology, 2026)
This study aims to map the conditions, challenges, and research opportunities in construction management, particularly in Manokwari City, West Papua, based on the Civil Engineering Study Program Research Roadmap 2025-2030. The method employed is a Systematic Literature Review (SLR) using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A total of 72 articles from international journals indexed in Scopus and Web of Science, as well as nationally accredited journals (SINTA 1 and SINTA 2), were systematically reviewed. The review focused on four research clusters: (1) Sustainable Construction, (2) Construction Risk, Safety, and Productivity Management, (3) Technology and Innovation in Construction Management, and (4) Quality Management. The results indicate that research related to construction management in West Papua, particularly Manokwari, remains severely limited, with significant research gaps especially in Building Information Modeling (BIM) implementation, locallygrounded risk management, and sustainable construction practices in archipelagic regions. This study contributes a comprehensive research map that can serve as a reference for academics, practitioners, and local governments in developing a sustainable and innovative construction industry in Manokwari.